Influence of cross-section geometry on air demand ratio in high-head conduits with a radial gate - Aydin, Alp Bugra; Baylar, Ahmet; Ozkan, Fahri; Tuna, Muhammed Cihat; Ozturk, Mualla (Iwa Publishing, 2021)
When the gate of a high-head conduit is partly opened, a negative pressure draws the air in through the air vent. Air that is entrained into the water is instantly forced downstream in the form of air bubbles. When the studies on high-head gated conduits were examined, it was determined that the air demand ratio varied depending on many hydraulic and geometric parameters. This work focused on determining the effect of conduit cross-section geometry on the air-demand ratio. A series of experiments were carried out on high-head radial gated conduits having different cross-section geometries. Experimental results showed that conduit cross-section geometry was an important effect on the air demand ratio especially in small gate opening rates. Further, design equations for the air demand ratio were presented relating the air demand ratio to Froude number, gate opening rate, and ratio of gate opening to conduit length.
Keywords: air demand; conduit; cross-section geometry; high-head flow; radial gate